Improving recruitment to clinical trials during pregnancy: A mixed methods investigation. (March 2018) - Strömmer, Sofia; Lawrence, Wendy; Rose, Taylor; Vogel, Christina; Watson, Daniella; Bottell, Joanne N.; Parmenter, Janice; Harvey, Nicholas C.; Cooper, Cyrus; Inskip, Hazel; Baird, Janis; Barker, Mary
Abstract: Objective: To identify reasons underlying women's refusal to participate in a pregnancy trial and to identify ways of increasing recruitment. Design: Mixed methods study using a questionnaire and qualitative interviews. Sample: A questionnaire asking them to indicate reasons for their decision was completed by 296 pregnant women who declined to participate in one of two trials of nutritional supplementation in a large teaching hospital in southern England. Qualitative interview data were collected from two samples of pregnant women: 1) 30 women who declined to participate in a trial but completed the questionnaire; and 2) 44 women who participated in a trial. Results: Questionnaire data from pregnant women who declined to participate suggested the major barriers to participation were study requirements, including taking study medication, having a bone scan or blood tests, or being too busy. Thematic analysis of interview data identified differences in self-efficacy and levels of trust in medical research between participants and decliners. Participants believed that the research would cause no harm, while decliners felt they or their unborn child would be at risk. When faced with potential obstacles, participants found ways around them while decliners felt they were insurmountable. Conclusions: Recruitment methods for pregnancy trials should focus on building women's trust in the trial, and on enhancing women's self-efficacy so they feel able to meet trial requirements. Suggestions for building trust include investing time in open, honest discussion of the risks and benefits of participation, improving visibility of the research team, testimonials from previous participants and advertising study safety and ethical conduct. Self-efficacy can be enhanced by training research staff in empowering styles of communication enabling women to feel heard and supported to problem-solve. These strategies could be implemented relatively easily into pregnancy trial protocols, and their effectiveness tested through their impact on recruitment rates. Highlights: Little is known why so many pregnant women refuse to participate in clinical trials. Most of what we know comes from trial participants rather than those who declined. Women who declined to participate in a clinical trial were interviewed and surveyed. A lack of trust in medical research was apparent in decliners (vs. participants). Strategies to improve trust and recruitment to trials in pregnancy are proposed.